Studies of interstellar matter on scales from 10AU to 10 kpc - Smith, Keith T. (2010)
This thesis presents four optical spectroscopic studies of absorption by matter in the diffuse interstellar medium on scales ranging from 10 AU to 10 kpc. The observations investigate two current problems in interstellar medium (ISM) research: small-scale structure (SSS), and the diffuse interstellar bands (DIBs).